Omnichannel: An Empirical Analysis among Indian Retail Banking Customers - Bhushan Bawankule, Arti Chandani (International Journal of Modern Agriculture, 2020)
Banking industry is going through a significant change due to technology and changing customer demand which is basically being more personalized and providing a more seamless banking experience. These changes have brought in Omni channel banking into practice. Aim: The purpose of this study is to understand the whether usage of banking channel is same across different genders and different age groups. The study also focuses on the security issues of personal and financial information with respect to digital banking among different age groups. The customer's experience in different banking channels and factors related to that channel are also being studied. Methodology: This research paper based on a quantitative analysis method. The Survey was done through an online questionnaire made on Google Forms to identify various factors that would influence the customer experience and inclination towards a specific banking channel. The respondents are customers of banks who are availing banking services from either Indian public sector or private banks. Result: There is a difference between gender and usage of banking channels while applying loan and managing accounts. In addition, protecting personal and financial information influences older age groups rather the younger ones. Moreover, customers using digital banking find that the advantages are time effectiveness, flexible working, seamless operation, and easy interaction with the bank. This helps in enriching their digital banking experience. Limitations: This study is only limited to the factors affecting Indian customer perspective in banking experience.